The Effect of Gadget Usage Duration on Cognitive Function with MMSE in SMPN 2 Students in Koba District, Bangka Belitung Islands - Fahrozi, Fahrozi; Nuraini, Nuraini; Darwin, Prasila; Leli H. Indriyati; Pudyastuti , Erlina (Jurnal EduHealth, 2023)
Gadgets as technological tools with its various conveniences are currently considered important in everyday life. The use of gadgets for a long duration time can interfere children's learning ability, reduce interaction with the surrounding environment and can reduce attention, resulting in impaired cognitive function’s development. This study aims to determine the relationship of gadget usage duration to the development of cognitive function. This is a descriptive analytic, cross-sectional study, which was conducted on SMPN 2 Koba students totaling 72 students. The SAS-SV questionnaire was used to determine the gadget usage duration (categorized as light, medium and heavy) and the MMSE questionnaire to examine cognitive function (categorized as normal and impaired cognitive function). The results showed that more than half of the subjects (56.9%) cognitive impairment and most (51.4%) were heavy gadget users. There is a significant relationship between the length of device use and the development of cognitive function (p=0.000). As a conclusion, the longer duration of gadget usage, the greater the possibility of impaired development of cognitive function.